Pemanfaatan Batu Sungai Maiting Toraja Utara Pada Campuran Laston AC-BC Dengan Variasi Temperatur Pemadatan - Sarira, Orion Yeheskel Samaa; Sariman, Syahrul; Nurdin, Abdul Rahim (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Damage to highways in Indonesia is often caused by the inadequate quality of asphalt compaction, which does not conform to the optimum temperature during on-site construction. Asphalt compaction is highly dependent on temperature to ensure the mix achieves maximum density, which strengthens the durability and service life of the road. This study explores the use of Maiting River stones from North Toraja Regency as materials in asphalt concrete binder course (AC-BC) mixtures, aiming to determine the characteristics and feasibility of the material.The research methods include material sampling, aggregate characteristic testing, mix design planning, specimen preparation, conventional Marshall testing, determining the optimum asphalt content (OAC), compaction temperature variations, and Marshall Immersion testing.The results show that the aggregate characteristics of Maiting River stones from North Toraja Regency indicate that the AC-BC mixture with 60/70 penetration asphalt comprises 58.75% coarse aggregate, 36.99% fine aggregate, and 4.27% filler, resulting in a design asphalt content of 5%. In this study, the optimum asphalt content used was 5.50%, with compaction temperature variations of 150°C, 180°C, and 200°C. The test results show that the optimum compaction temperature for the asphalt mixture (AC-BC) is 150°C, achieving Stability of 1575.89%, Flow of 3.15%, FMA of 15.08%, VIM of 3.12%, VFB of 79.29%, and MQ of 499.94%. These values meet the standards specified in the 2018 Bina Marga specifications.